2016
DOI: 10.1371/journal.pone.0160433
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Body Organelles within the Parasite Trypanosoma cruzi: A Role for Intracellular Arachidonic Acid Metabolism

Abstract: Most eukaryotic cells contain varying amounts of cytosolic lipidic inclusions termed lipid bodies (LBs) or lipid droplets (LDs). In mammalian cells, such as macrophages, these lipid-rich organelles are formed in response to host-pathogen interaction during infectious diseases and are sites for biosynthesis of arachidonic acid (AA)-derived inflammatory mediators (eicosanoids). Less clear are the functions of LBs in pathogenic lower eukaryotes. In this study, we demonstrated that LBs, visualized by light microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 66 publications
1
81
0
Order By: Relevance
“…In Leishmania, the presence of PLA 2 and prostaglandin F 2α synthase on parasite LDs has been identified . In addition to the presence of PGE synthase on LDs, the accumulation of arachidonic acid and PGE 2 formation on LDs was also reported in T. cruzi . The production of inflammatory mediators by parasite LDs suggests that this organelle participates in an elaborate form of evasion of the immune system, and it is even suggested that parasite LDs could be classified as a mechanism of pathogenicity …”
Section: Lds and Protozoan Interactionsmentioning
confidence: 98%
See 2 more Smart Citations
“…In Leishmania, the presence of PLA 2 and prostaglandin F 2α synthase on parasite LDs has been identified . In addition to the presence of PGE synthase on LDs, the accumulation of arachidonic acid and PGE 2 formation on LDs was also reported in T. cruzi . The production of inflammatory mediators by parasite LDs suggests that this organelle participates in an elaborate form of evasion of the immune system, and it is even suggested that parasite LDs could be classified as a mechanism of pathogenicity …”
Section: Lds and Protozoan Interactionsmentioning
confidence: 98%
“…In both infections, PGE 2 production was reported as permissive to pathogens and probably downmodulate macrophage antimicrobial response . Furthermore, PGE 2 not only affects infected leukocytes but may also inhibit Th1 responses, which would favor pathogen proliferation and dissemination . Moreover, LDs in colon cancer cells are active organelles involved in PGE 2 synthesis and may have implications in the pathogenesis of adenocarcinoma of the colon …”
Section: Ld Functions In Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of ATGL, genetically or pharmacologically, also impairs eicosanoid release in other types of immune cells, such as neutrophils [79]. In the intracellular parasites Leishmania and Trypanosoma , LDs can also act as a source of immunomodulatory prostaglandins implicated in improving the survival of the parasite within its host [80, 81]. The available evidence suggests that the enzymatically released AA is locally metabolized, as both eicosanoid precursors and eicosanoid producing enzymes have been found associated with LDs [75].…”
Section: 12 Storage Of Vitamins and Signaling Precursorsmentioning
confidence: 99%
“…While conventional Raman analysis can be useful, to first order the long-chain polyunsaturated fatty acids (LC-PUFA) appear nearly identical, with the vibrational modes of most moieties degenerate, redundant or very broad [5] [6] [7] [8] [9]. But logically this cannot be the case, because the LC-PUFA are so vastly different biochemically.…”
Section: Introductionmentioning
confidence: 99%